Two Sides of the Same Coin: Tendoligamentous Similarities and Dissimilarities of Great Toe and Thumb Anatomy on MRI - Rajani, Heena; Singh, Dharmendra Kumar; Suman, Saurabh; Katyan, Amit; Sharma, Anuradha; Kumar, Nishith (Indian Journal of Radiology and Imaging, 2022)
Evolution and functional necessities have compelled the great toe of the foot and its embryological kin, thumb, to have some tendoligamentous differences with a similar basic anatomical structure. This provides biomechanical advantage to these joints: the thumb is apposable and more mobile, ensuring hand dexterity and tool-handling, whereas the great toe is less mobile and more stable, ensuring weight bearing, strength, and stability for bipedal locomotion. This pictorial review will methodically illustrate the similarities and dissimilarities of the joint morphology and its tendoligamentous attachments at the level of carpometacarpal joint, metacarpophalangeal joint, and interphalangeal joints of thumb compared with tarsometatarsal joint, metatarsophalangeal joint, and interphalangeal joints of great toe. It intends to provide a comprehensive understanding of the normal anatomy of great toe and thumb to the radiologists, enabling better interpretation of the pathologies.
Keywords: MRI; great toe; thumb; hallucis; pollicis